Study on the ambulatory monitoring and optimization measures of the Gas wells in block A - Yan Shujuan (E3S Web of Conferences, 2022)
The analysis of the Gas well is the core work and accompanying with the whole process of gas field development. The dynamic monitoring technology of gas well is an effective way to provide theoretical basis for dynamic analysis. Now there are 3 normal production gas Wells in the production test area of block A. In the process of production, pressure recovery, hydrostatic pressure and corrosion monitoring were carried out for the changes of production, pressure, fluid physical properties and underground surface engineering.We know the fluid accumulation, the corrosion of the downhole string, the reservoir characteristics, the reservoir physical parameters by these monitoring activities. So we guide the reasonable production of gas Wells timely and effectively, in order to better provide a basis for gas well production management and scientific decisionmaking. We should carry out rectification and strengthen management to problematic gas Wells and loopholes in dynamic monitoring, and provide better assurance for the development of gas fields.